Pride and Prodigies : Studies in the Monsters of the Beowulf Manuscript - Orchard, Andy (Book collections on Project MUSE., 2015)
In this series of detailed studies, Andy Orchard demonstrates the changing range of Anglo-Saxon attitudes towards the monstrous by reconsidering the monsters of Beowulf against the background of early medieval and patristic teratology and with reference to specific Anglo-Saxon texts.